Enabling enhanced lithium storage capacity of two-dimensional pentagonal BN2 by aluminum doping - Thanasee Thanasarnsurapong; Panyalak Detrattanawichai; Klichchupong Dabsamut; Kodchakorn Simalaotao; Tosapol Maluangnont; Adisak Boonchun (Journal of Materials Chemistry C, 2023)
The highest theoretical Li storage capacity (2297 mA h g −1 ) to date in a pentagonal structure, achieved through aluminum-for-boron substitution in penta -BN 2 .
Keywords: MXene and MAX Phase Materials; 2D Materials and Applications; Inorganic Chemistry and Materials